Relationship between presenting symptoms and tumor location in colorectal cancer patients - Ismida, Fitri Dewi; Maghfirah, Desi; Salam, Nurbahri L; Yusuf, Fauzi; Mulia, Vera Dewi; Purnomo, Avisena Gatot (Universa Medicina, 2024)
BackgroundColorectal cancer (CRC) often shows symptoms at an advanced stage, causing delayed diagnosis and poorer prognosis. Initial symptoms, or chief complaints, are usually identified through patient history and can vary based on tumor location. This can help in establishing a diagnosis. This study aimed to determine the relationship between presenting symptoms and tumor location in CRC patients at Zainoel Abidin Regional General Hospital, Banda Aceh. Methods This cross-sectional study was conducted using secondary data from medical records (2019–2022) for 163 CRC patients. Information on symptoms of patients were collected from patient files: anemia, anorexia, diarrhea, constipation, abdominal pain, rectal bleeding, and palpable abdominal mass. Tumor locations were classified as right colon, left colon, rectum, and left colon plus rectum. Bivariate analysis was used to analyze the data. Results Of the 163 patients, 98 (58%) were aged e”50 years, 82 (50.3%) were male, and 99 (60.7%) had rectal tumors. The percentage of patients presenting with rectal bleeding was significantly higher in rectal cancers (47.47%) as compared with cancers in the left colon (28.57%) and left colon and rectal (33.33%) cancers (p=0.000). The percentage of patients presenting a palpable abdominal mass was significantly higher in right colon (31.58%) compared with left colon (4.76%) and rectal cancer (1.01%) (p=0.000). ConclusionsTumor location in the right colon is associated with palpable abdominal mass, while rectal location is associated with rectal bleeding in CRC patients. Familiarity with clinical symptoms of CRC could make patients more sensitive to undergo more frequent screening for cancer.